2000
DOI: 10.1161/01.cir.101.2.165
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Derived Nitric Oxide Contributes to the Regulation of Venous Tone in Humans

Abstract: Background-Although nitric oxide (NO) is known to play an important part in the regulation of arterial tone, little is known about its role in veins. The aim of this study was to investigate the role of basal and stimulated NO activity in the regulation of tone of the human venous capacitance bed. Methods and Results-We measured venous tone using radionuclide forearm venous plethysmography in 24 healthy subjects with no cardiovascular risk factors. In 13 subjects, basal NO activity was assessed by measuring th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 41 publications
1
42
0
1
Order By: Relevance
“…Despite evidence for a well-defined role of NO in the venous vasculature (14,40), NOS inhibition in either group did not result in differences in venous vascular function measured by the VVV. Deep veins of the legs have sparse SNS innervation; thus, their compliance is primarily controlled by surrounding skeletal muscles under normal physiologic conditions (41).…”
Section: Discussionmentioning
confidence: 69%
“…Despite evidence for a well-defined role of NO in the venous vasculature (14,40), NOS inhibition in either group did not result in differences in venous vascular function measured by the VVV. Deep veins of the legs have sparse SNS innervation; thus, their compliance is primarily controlled by surrounding skeletal muscles under normal physiologic conditions (41).…”
Section: Discussionmentioning
confidence: 69%
“…Deteriorated vessel wall function (venous or arterial) could promote thrombus formation. The link between endothelial dysfunction and venous thrombosis has been established in several studies 46) and, interestingly, endothelial microparticles, which have been shown to regulate venous tone, were detected in patients with venous thrombosis 47,48) . Since more than 70% of the total circulating blood volume is contained in the venous vascular bed, it is conceivable that small changes in venous tone may substantially affect filling pressure, making the evaluation of venous endothelial function an attractive new method to evaluate vascular homeostasis.…”
Section: Determination Of Venous Endothelial Dysfunctionmentioning
confidence: 98%
“…by assessing ex vivo the contraction of rings of vein tissue excised at surgery (30,31), or by a minimally invasive method which assesses the diameter of a dorsal vein of the hand in response to pharmacologic stimuli (32). The studies so far performed using these methods show that NO plays a central role in the regulation of venous endothelial function, similarly to what it does for arterial endothelial function (33,34). Interestingly, what emerges from these studies is that conditions associated with arterial endothelial dysfunction, like hypertension, smoking, diabetes, coronary artery disease, heart failure and renal failure, are also characterised by a dysfunction of venous endothelium (30,31,(35)(36)(37)(38)(39)(40)(41)(42) …”
Section: Endothelial Dysfunction and Thrombosismentioning
confidence: 99%